Using Two-Way Prestressed Semicircular Steel Plate for Construction of Reinforced Concrete Cylinder Column. (30th July 2018) - Ren, Zhenhua; Zeng, Xiantao; Sun, Junbo
Abstract : A concrete column has a significant influence on constructions because the component withstands the major weight of the whole structure. However, the ordinary concrete column has limited capacity to resist to multiaxial loadings. Since steel plate is one of the most common materials used in construction, concrete reinforced with steel plates based on prestressing reinforcement technology would be a directly applicable solution to the enhancement of mechanical property. In this study, a new reinforcement method upon concrete cylinder column used a two-way prestressed semicircular steel plate, which has already been patented. The study firstly analyzed the stress-bearing situation of the short concrete column reinforced by a two-way prestressed semicircular steel plate. The considerable substitution effect of vertical prestressing force on the concrete column was explored. The multiple restriction effects of horizontal prestressing force, semicircular steel plate, and stirrup were examined. Thereby, the calculation model was derived for the prestressed structure. Secondly, the formula was verified by experiments with close agreements. The result indicated that a unified strength theory was applicable to the theoretical calculation for short concrete column reinforced with a prestressed semicircular steel plate under axial compression, providing the foundation for analytical computation of prestressed semicircular steel plate-reinforced concrete column structures.